Risk Management Plans: reassessment of safety concerns based on Good Pharmacovigilance Practices Module V (Revision 2)-a company experience - Suzan Esslinger; Linda Quinn; Sami Sampat; Marijo Otero-Lobato; Wim Noël; Anja Geldhof; Nicole Herijgers; Sarah-Jane Reeder (BMC, 2022)
Abstract Introduction In the European Union (EU), a Risk Management Plan (RMP) is submitted as part of the dossier for initial marketing authorization of a medicinal product or with an application involving a significant change to an existing marketing authorization. A comprehensive revision of the EU Guideline on Good Pharmacovigilance Practices (GVP) Module V-Risk Management Systems (Revision [Rev] 2), adopted in March 2017, provides a framework for developing more focused, actionable, and risk-proportionate RMPs. This paper describes the Janssen experience with the interpretation and application of GVP Module V (Rev 2) regarding the evaluation of safety concerns in an RMP. Methods Janssen convened a cross-functional working group to promote consistent interpretation of the GVP Module V (Rev 2) guidance across therapeutic areas. The group created 3 algorithms to support implementation of the guidance related to removal or reclassification of safety concerns by product-specific RMP teams. Results Following implementation of the GVP Module V (Rev 2) guidance, the algorithm-driven process led to a substantial decrease in the number of safety concerns for most products. With few exceptions, EU health authorities agreed with the proposed safety concern removals or reclassifications, resulting in RMPs that were focused on only those safety concerns that required further characterization or specific risk minimization. Conclusions The algorithm-driven process allows for consistent interpretation and application of the GVP Module V (Rev 2) guidance, which enables product teams to develop an actionable RMP using a thoughtful, evaluative, science-based approach that considers all available evidence.